Learning object-oriented JavaScript - Fhala, Ben; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2014)
"One of the most common issues faced by JavaScript developers is what is known in the industry as 'spaghetti code.' This issue is common when developers don't know how OOP works, as they end up creating layers of code on top of each other, resembling spaghetti. The goal of OOP is to organize your code and make your life easier. This course will help you change some common coding practices and empower you by giving you the tools you need for more efficient development. You start with building a simple digital clock and use this as the case sample for the course. Then, we begin exploring the object-oriented tools in JavaScript such as the constructor, scope, methods, and properties. Next, we dive even deeper as we explore the wonderful world of prototypes, static methods and properties, and namespaces. We then turn our attention to inheritance and finally end the course with a section to dedicated events and callbacks. As we explore what they are and how to use them, we complete our sample by creating a fully usable alarm clock. With this course, you will be an expert in OOP with JavaScript in under 3 hours!"--Resource description page.
Title and date of publication from resource description page (Safari, viewed July 12, 2016).
Presenter, Ben Fhala.
Keywords: JavaScript (Computer program language); Object-oriented programming (Computer science); Electronic books